Using agriculture to improve child health: Promoting orange sweet potatoes reduces diarrhea - Jones, Kelly M.; de Brauw, Alan (Elsevier, 2015)
Vitamin A deficiency (VAD) is prevalent throughout the developing world, and causes night blindness and increases child morbidity and mortality. We studied the health benefits of biofortification in reducing VAD, using a cluster-randomized impact evaluation in 36 villages in northern Mozambique. Based on a sample of 1,321 observations of children under the age 5, biofortification reduced diarrhea prevalence by 11.4 percentage points (95% CI 2.0–20.8), and by 18.9 percentage points in children under the age three (95% CI 6.6–68.3). Diarrhea duration was also reduced. This is promising evidence that child health can be improved through agricultural interventions such as biofortification.